2006
DOI: 10.1128/cvi.13.1.162-164.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing and Hemagglutination-Inhibiting Activities of Antibodies Elicited by the 2004-2005 Influenza Vaccine against Drifted Viruses

Abstract: The appearance of these two drift variants was reflected in the epidemiological patterns observed in Italy in the 2002-2003 and 2004-2005 seasons; about 5,000,000 cumulative cases of influenza-like illness were reported in each of these two seasons, while during the mild epidemic season, the estimated number of cases ranged between 2.5 million and 4 million. In particular, during the early months of 2005, the Italian surveillance network observed the highest incidence in the Ն65-yearold group, since the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…It should also be recognised that titres measured in HI assays, unlike microneutralisation, do not necessarily represent functional antibodies and the threshold of 40 conventionally applied as indicative of sero-protection may not predict immunity to zoonotic infections [17][18][19][20][21]. In general, HI is thought to overestimate cross-reactive heterologous versus homologous responses, and given that A(H3N2) v is slightly more divergent from ancestral strains in its HA1 than is F844, there may be additional reason to consider our results optimistic [18][19][20][21]. Conversely, other markers such as cell-mediated immunity may also contribute to protection but were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be recognised that titres measured in HI assays, unlike microneutralisation, do not necessarily represent functional antibodies and the threshold of 40 conventionally applied as indicative of sero-protection may not predict immunity to zoonotic infections [17][18][19][20][21]. In general, HI is thought to overestimate cross-reactive heterologous versus homologous responses, and given that A(H3N2) v is slightly more divergent from ancestral strains in its HA1 than is F844, there may be additional reason to consider our results optimistic [18][19][20][21]. Conversely, other markers such as cell-mediated immunity may also contribute to protection but were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In particular, the DNA rates [assessed as serum haemagglutination-inhibiting (HI) assay titers ≥ 40 IU]. [15][16][17] Several observational studies demonstrated a reduction of vaccine effectiveness in seasons in which a mismatch between vaccine and circulating strains occurred. A randomized placebo-controlled trial conducted to evaluate effectiveness and cost benefit of influenza vaccination of healthy working adults showed a strong correlation between antigenic drift and vaccine effectiveness decrease.…”
Section: New Potential Influenza Vaccine Optionsmentioning
confidence: 99%
“…As reported in [3], influenza causes up to 300,000 excess hospitalizations and up to 40,000 excess deaths, among the high-risk population. Therefore, substantial public health implications arise from the decisionmaker perspective when programming an annual vaccination strategy.…”
mentioning
confidence: 94%
“…It is widely accepted from clinical study that hemagglutination inhibition antibody levels could be used as a surrogate of protective activity. This correlation is stronger when the antigene is very close to the vaccine strain and the neutralizing assay could be considered as a valid alternative to quantify the immune response [3].…”
mentioning
confidence: 99%